Tutorial for navigating the interactive version of the atlas of common bean production in Africa (2nd ed.) - Castaño, Silvia Elena (Pan-Africa Bean Research Alliance, 2020)
This tutorial is a reference tool to facilitate the use of the online Atlas as an information source for users interested in common bean production in Africa. Online interactive Atlas available at: http://gisweb.ciat.cgiar.org/atlasbean/ A pdf version of the Atlas of Common Bean Productin in Africa - 2nd Edition - is available at https://hdl.handle.net/10568/110556